Anti-inflammatory activities of Canarium subulatum Guillaumin methanol extract operate by targeting Src and Syk in the NF-κB pathway. (28th June 2019) - Choi, Eunju; Kim, Mi-Yeon; Cho, Jae Youl
Abstract: Ethnopharmacological relevance: Canarium subulatum Guillaumin is an herbal medicinal plant native to Southeast Asia. Ethnopharmacological evidence suggests that plants of the genus Canarium cure a variety of inflammatory diseases. Aim of the study: The pharmacological mechanisms of C. subulatum Guillaumin remain poorly understood. In this study, we investigate inflammatory mechanisms and target molecules using C. subulatum Guillaumin methanol extract (Cs-ME) in inflammatory reactions managed by macrophages. Materials and methods: To identify the anti-inflammatory activities of Cs-ME, lipopolysaccharide (LPS)-stimulated macrophages and a murine HCl/EtOH-induced gastritis model were chosen. The luciferase reporter gene assay, Western blot analysis, overexpression strategy, and the cellular thermal shift assay (CETSA) were employed to investigate the molecular mechanisms and target enzymes of Cs-ME. The active ingredients of this extract were also determined by HPLC. Results: Released levels of nitric oxide (NO) and mRNA expression levels of iNOS and IL-6 were downregulated by Cs-ME without exhibiting cytotoxicity. This extract inhibited MyD88-induced promoter activity and the nuclear translocation of nuclear factor (NF)-κB. Moreover, we found that Cs-ME reduced the phosphorylation of NF-κB upstream signaling molecules including IκBα, IKKα/β, Src, and Syk in LPS-stimulated macrophage-like RAW264.7 cells. The results of Western blot and CETSA confirmed that Src and Syk are anti-inflammatory targets of Cs-ME. In addition, orally injected Cs-ME alleviated HCl/EtOH-induced gastric ulcers in mice. HPLC analysis indicated that quercetin, luteolin, and kaempferol are major active components of this extract with anti-inflammatory activity. Conclusions: Cs-ME exhibits anti-inflammatory effects in vitro and in vivo by targeting Src and Syk in the NF-κB signaling pathway. Consequently, Cs-ME could be developed as an anti-inflammatory herbal medicine. Graphical abstract: Image 1